Ecocide - Neira, Hernán; Russo, Lorena Inés; Álvarez Subiabre, Bernardita (Revista de Filosofía, 2019)
Current human technical capacities may produce a world scale ecocide. It is convenient to give a theoretical foundation to the fact that ecocide must be considered a crime that affects the whole humanity. The concept of ecocide arises in the context of war theory and right. Since then, the concept relocates into common language and, recently, into environmental philosophy. Ecocide shares also some aspects of homicide and ecological suicide and, therefore, it is linked with the theory willing death and with that one of self exposition to death risk, not of an individual, but of humanity.